Planning the External Sector: techniques, problems and policies - United Nations. Centre for development planning,projections and policies (New York, 1967)
This is the interregional seminar on development planning, organized by the centre for development planning, projection and policies in cooperation with the Bureau of technical assistance operation.
aia 12/02/2019
Loans
Keywords: Economic development; Commercial policy; Regional planning; Developing countries